Seroprevalence of helicobacter pylori infection in couples. - Perez-Perez, G I (1991)
We investigated the prevalence of Helicobacter pylori in 277 couples attending an infertility clinic. In total, 96 (17.3%) of the 554 persons were positive; in only 18 (6.6%) of the couples were both persons seropositive. Age was an important predictor for H. pylori infection. For 177 couples, information regarding birthplace, duration of cohabitation, history of ulcer or gastritis, and use of antacid or bismuth compounds was available. None of these variables correlated with H. pylori infection except place of birth; 69.1% of 55 persons born outside the United States were seropositive compared with 8.7% of persons born within the United States (P less than 0.0001). Being a partner of an H. pylori-infected person increased the risk of being infected; however, by multiple logistic regression analysis this effect was entirely explained by age and national origin. These data suggest that in young sexually active adults, person-to-person transmission of H. pylori does not occur or at most occurs infrequently.